Efektifitas Hasil Belajar Passing Bawah Permainan Bola Voli dengan Metode Example Non-Example - Ilyas Hidayat; Ilham Arvan Junaidi; Hengki Kumbara (Departement of Mathematics Education, 2023)
This study aims to determine the effective example non-example learning model for class XI student learning outcomes at SMA Negeri 11 Palembang in carrying out underhand passing in a volleyball game. The method used in this study is the experimental research method. The type of research used in this research is Pre-Experimental Design. Using the design form